Physical Activity Patterns Over 10 Years in Relation to Body Mass Index and Waist Circumference: The Whitehall II Cohort Study. (13th June 2013) - Hamer, M.; Brunner, E.J.; Bell, J.; Batty, G.D.; Shipley, M.; Akbaraly, T.; Singh‐Manoux, A.; Kivimaki, M.
<x xml:space="preserve">Abstract</x> Objective Physical activity patterns over 10‐years in relation to changes in body mass index (BMI) and waist circumference (WC) were examined. Design and Methods Participants (4, 880, mean age 49.3 years at baseline) from the Whitehall II cohort study were included. Self‐reported physical activity and anthropometric data were collected at baseline (1991) and twice during follow‐up (1997 and 2002). Results At baseline, meeting established guidelines for physical activity, particularly through vigorous activity, was associated with lower WC (multivariable adjusted B compared to not meeting the guidelines −2.08 cm, 95% CI, −1.39, −0.75) and BMI (−0.34 kg/m2, −0.10, −0.59). Based on repeat data, "high adherence" to the guidelines compared to "rare adherence" over follow‐up was associated with lower BMI (adjusted difference, −0.43 kg/m2, 95% CI, −0.79, −0.08) and WC (−2.50 cm, 95% CI, −3.46, −1.54) at follow‐up. Compared to participants that remained stable between 1997 and 2002 (change of <2.5 h/week), those that reported an increase in moderate‐vigorous physical activity of at least 2.5 h/week displayed lower BMI (−0.40 kg/m2, 95% CI, −0.71, −0.08) and WC (−1.10 cm, 95% CI, −1.95, −0.75). Conclusion Regular physical activity, confirmed by repeated assessments, is associated with relatively favorable levels of adiposity markers after 10 years follow‐up.